Skilled interpersonal communication research, theory and practice - Hargie, Owen (Routledge, 2022)
Established as the foremost textbook on communication, the seventh edition of Owen Hargie's Skilled Interpersonal Communication is thoroughly revised and updated with the latest research findings, theoretical developments and applications.